MINAT SISWA MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI INDONESIA - Rukayah Siti Masitah Hutabarat; Sri Hayati Damanik; Marnita Sipahutar; Muhammad Rifai (STAI Bahriyatul Ulum Pandan, 2025)
This research aims to determine the factors that influence the interest of Class XII students in proceeding their instruction to state and private colleges in Indonesia. The population in this study were all 199 Class XII students, consisting of 96 male students and 103 female students from Class XII Science and Social Studies, while the sample in this study were 31 male students and 35 female students from Class XII Science 3 and Social Studies 3, so the total sample was 66 people. The subjects in this study were teachers and students, while The object is students' interest in continuing their studies to tertiary level. The data collection techniques used questionnaires, interviews, and documentation. The data analysis technique used product moment. The results of the research conducted at SMA Negeri 1 Kolang show that the factors that influence interest are in the high category with a percentage of 6%, students are in the medium category with a percentage of 12%, and students are in the low category with a percentage of 82%. Data taken from a sample of 66 students at SMA Negeri 1 Kolang shows that internal factors that influence students' interest are classified as moderate, and external factors that influence interest in continuing studies to university are in the high category at 22.72% (15 students), 45.45% (30 students) in the medium category, and 31.81% (21 students) in the low category. Thus, it can be seen that external factors that influence interest in continuing studies to university are only in the medium category for 30 students, and the remaining 21 students are in the low category, and there is not a single external factor that influences interest in continuing studies to university in the high category.